Ownership structure and corporate governance: What does the data reveal about Saudi listed firms? - Mamdouh Abdulaziz Saleh Al-Faryan; Everton Dockery (Corporate Ownership & Contol, 2017)
In this paper we examine the ownership structure of 169 firms listed on the Saudi Arabian stock market from 2008 to 2014. The analysis uses the testing methodology described by Demsetz and Lehn (1985) to examine the effects of firm and market instability on Saudi ownership structure and additionally, the effect of systematic regulation that imposes constraints on the behaviour of the selected listed firms. We find evidence, for the majority of the ownership structures considered, in favour of the view that firm size, regulation and instability affects ownership structure. The results suggest that the size variable has a positive effect on ownership concentration. Our analysis also shows that instability had some effect on ownership concentration and structure when using the non-linear specification, particularly when using firm specific instability, albeit the effect was stronger when the instability measure was accounting profit returns. Lastly, there is evidence that government-owned firms were mostly affected by regulation while diffused owned firms were affected most by instability than non-government owned firms.
Keywords: G10; G30; G32; L10; 330; Ownership Structure; Ownership Concentration; Market Instability; Control Potential